Parents' assessments on the effectiveness of nonaversive behavior management techniques: A pilot study - Özgür Önder Kuşcu; Eşber Çağlar; Nüket Sandallı (Elsevier, 2014)
Background/purpose: Dental treatment for children often requires the use of behavior management techniques (BMTs). The aim of this pilot study was to determine the effectiveness of nonaversive BMTs by the ratings of parents who had observed their children during three sequential dental treatment sessions. Materials and methods: Dental records of 47 children (age 5-13 years) who had received at least three sessions of dental treatment, two of which included local anesthesia administration, were analyzed retrospectively. Twenty-five out of 47 invited parents agreed to participate in the study. The parental form of the Children's Fear Survey Schedule - Dental Subscale was used for determining children's anxiety. Parents were asked to fill in a questionnaire after watching a descriptive video on eight widely-accepted BMTs to rate the effectiveness of each applied BMT on a 10-grade visual analog scale (VAS). Results: All nonaversive BMTs were considered by the parents to be very effective on children's favorable behavior with a mean VAS score of 9.25. Perceived control and positive reinforcement were rated the most (VAS score: 9.80 and 9.52; P > 0.05). Conclusion: All nonaversive BMTs were found to be effective by some Istanbulian parents on children's favorable behavior.